2023
DOI: 10.3390/tropicalmed8020111
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Infection Intensity of Human and Animal Tungiasis in Napak District, Karamoja, Northeastern Uganda

Abstract: Tungiasis is an important but highly neglected cause of morbidity in resource-poor communities in Latin America and sub-Saharan Africa. Data upon which implementation of control measures can be based are scarce. Before piloting an integrated tungiasis control program in three parishes of Napak district, Uganda, a cross-sectional survey involving the systematic examination of humans and domestic mammals was implemented to establish the occurrence patterns of tungiasis. The study population was 5482 residents, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 69 publications
(158 reference statements)
1
38
0
Order By: Relevance
“…The high prevalence of tungiasis infection (61.0%) among the interviewed household caretakers corresponds with the prevalence of 62.8% among the overall population in our study area in Napak district, northeastern Uganda [15]. Tungiasis is known to be endemic in Uganda, especially in rural communities in Eastern regions, where a study found that in 22.5% of households, tungiasis infection was present in at least one household member [46].…”
Section: Stigma In a Hyperendemic Environmentsupporting
confidence: 75%
See 4 more Smart Citations
“…The high prevalence of tungiasis infection (61.0%) among the interviewed household caretakers corresponds with the prevalence of 62.8% among the overall population in our study area in Napak district, northeastern Uganda [15]. Tungiasis is known to be endemic in Uganda, especially in rural communities in Eastern regions, where a study found that in 22.5% of households, tungiasis infection was present in at least one household member [46].…”
Section: Stigma In a Hyperendemic Environmentsupporting
confidence: 75%
“…Population-based studies have shown high prevalence of tungiasis, for example, 25% in rural Kenya [4], 45% in rural Nigeria [11], and 43% in Brazilian fishing villages [12], and very severe cases with hundreds of sand fleas have been described in Tanzania, Colombia, and Madagascar [2,13,14]. In Napak District, rural northeastern Uganda, our study team recently found extremely high tungiasis prevalence of 62.8% [15]. Despite its endemic presence in many countries, tungiasis has been neglected by healthcare professionals and researchers alike [1,16].…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations